How Can Governmental Positive Power Decrease Violence in Crime-Oriented Arenas?: the Case of English Football - Guy, Shlomit (International journal of offender therapy and comparative criminology, 2018)
This article will survey the dramatic change English football had undergone since the end of the last century. The authors will closely explore the implementation of the Taylor Report recommendations, to convince that which power and management techniques were used to decrease violence in public areas that were previously considered dangerous and crime-oriented. It will be argued that disciplinarian techniques were practiced, much like those described in Foucault’s Discipline and Punish, while this very power has proven to be positive and revitalizing. It will be therefore concluded that power is at its most effective when operated via techniques of discipline and social inclusion. These arguments correspond with the positive criminology theory whose popularity within the discipline is gradually increasing.